Some Policy Reflections on Art. 12B UN Model on Automated Digital Services. A Reasonable Alternative? - de Goede, Jan J.P. (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article deals with policy aspects related to the introduction to the new Art. 12B as to be included in the 2021 update of the 2017 UN Model Double Taxation Convention between Developed and Developing Countries dealing with the elimination of double taxation of income from automated digital services. The Author discusses the draft article itself and ends with some evaluation and conclusions as to whether Art. 12B can be considered a reasonable alternative compared to the so-called Pillar I approach as included in the so-called Blueprint published by the OECD in close co-operation with the BEPS Inclusive Framework.